The Battle for Rya Forest: A Case Study of Conservation and Modernisation in Sweden, 1910–1960* - Björn Billing (Journal for the History of Environment and Society)
Rya Forest is a small area of green space in Gothenburg surrounded by an industrial district in connection with the port. This broadleaf forest was protected in 1928 based on the first Swedish Nature Conservation Act of 1909. In the decades that followed, Gothenburg underwent rapid urban expansion and modernisation, which generated conflicts of interest that culminated in the late 1950s when plans were launched to place a sewage treatment plant in Rya Forest. An extensive public debate took off and one daily newspaper even called the matter “the major nature conservation issue of this generation”. This article examines the history of the nature reserve with particular focus on the controversy over the treatment plant. Discourse analysis reveals diverging ideas about nature, society, tradition and progress. Rya Forest nature reserve is also an example of how the law of 1909 could be repealed in favour of industry and infrastructure. Furthermore, the case illustrates a growing awareness among conservationists of how seemingly wild landscapes actually have been shaped by human land use, and also how postwar modernisation meant new challenges for conservation organisations regarding the balance between local and national efforts.